2013
DOI: 10.1088/2040-8978/15/7/075407
|View full text |Cite
|
Sign up to set email alerts
|

An image domain approach to the interpretation of the visible moiré phenomenon

Abstract: An approach to the interpretation of the visible moiré phenomenon in the image domain has been proposed. The analysis of the Fourier series expansion presents an initial criterion for distinguishing the real moiré and pseudo-moiré cases. A geometric calculation of the superposed grating lines is utilized to obtain the parameters for describing the real and pseudo-moiré cases. On the basis of the study, the average intensities of the waveforms of the real moiré and pseudo-moiré cases are calculated in order to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(6 citation statements)
references
References 11 publications
0
6
0
Order By: Relevance
“…The moiré technique has also been applied to the structural illumination microscopy [6,7]. Yu et al [8,9] worked on the visible moiré patterns and the influence of different grating frequencies on the resulting moiré patterns. Joydeep [10] has shown a method for experimental variation of shape of the moiré patterns generated using interferometry and a Spatial Light Modulator.…”
Section: Literature Surveymentioning
confidence: 99%
“…The moiré technique has also been applied to the structural illumination microscopy [6,7]. Yu et al [8,9] worked on the visible moiré patterns and the influence of different grating frequencies on the resulting moiré patterns. Joydeep [10] has shown a method for experimental variation of shape of the moiré patterns generated using interferometry and a Spatial Light Modulator.…”
Section: Literature Surveymentioning
confidence: 99%
“…However, the results of this analysis yield complex frequency components. In 2013, a Moiré pattern analysis of overlapping gratings with varying phases was presented [67]. The technique used was based on Fourier series expansion combined with geometric methods.…”
Section: Introductionmentioning
confidence: 99%
“…The transparent and opaque lines of the two panels have entirely different light intensities. It relies on AND and OR operators to represent overlapping results, similar to the idea in this article [67]; however, we define a set of data as opaque and transparent line segments with a Fourier series of rectangular signals. The revealing grating (used as a reference) has a constant duty cycle value of 0.5, whereas the base grating is assigned a value between 0 and 1.…”
Section: Introductionmentioning
confidence: 99%
“…Blau et al [5] and Röhrich et al [6] used moiré in structural illumination microscopy. Yu et al [7,8] has performed an in-depth image domain study of the visible moiré patterns. Yu et al [8] has also showed generation of different moiré patterns for different period ratios of the gratings used to produce the moiré patterns.…”
Section: Introductionmentioning
confidence: 99%